Perilaku Pencarian Informasi Mahasiswa Psikologi Universitas Katolik Soegijapranata dalam Praktik Pendampingan Orang Sakit - Edy Wijayanto; Lydia Christiani (Jurnal Ilmu Perpustakaan, 2024)
The research discusses the information seeking behavior of students in the Psychology Study Program at Soegijapranata Catholic University, fourth semester, class of 2019-2021 in implementing the practice of assisting sick people. The aim is to determine the information-seeking behavior of students at the Fourth Semester Soegijapranata Catholic University Psychology Study Program in Implementing Practices for Accompanying the Sick. The qualitative method is the method used in this research. Data collection was carried out by interviewing informants. The results of the research analysis show that fourth semester students of the Soegijapranata Catholic University Psychology Study Program, in carrying out the practice of assisting sick people, have the ability to search for information that is classified as accurate and precise. What is meant by accuracy and precision is that when students already know the steps in searching for information, and already know the right sources for looking for information regarding assisting sick people, then students will get the information they need.